2010
DOI: 10.1080/03601230903471878
|View full text |Cite
|
Sign up to set email alerts
|

Fate of14C-ethyl prothiofos insecticide in canola seeds and oils

Abstract: Canola plants were treated with (14)C- prohiofos under conditions simulating local agricultural practices. (14)C-residues in seeds were determined at different time intervals. At harvest time about 32 % of (14)C-activity was associated with oil. The methanol soluble (14)C-residues accounted for 12 % of the total seed residues after further seeds extraction, while the cake contained about 49 % of the total residues. About 69 % of the (14)C-activity in the crude oil could be eliminated by simulated commercial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Compound O,O-diethyl S-hydroxymethyl phosphorodithioate (VI) was detected as a conjugated metabolite, and its concentration was 0.004 ppm ( Table 7). This result agrees with some previous studies, 5,33,34 which noted that in adult rats, prothiofos gave prothiofos oxon, O-ethyl phosphoric acid, and 2,4-dichlorophenole. Fenitrothion insecticide was converted to phosphorothioate and dimethylphosphate.…”
Section: ■ Materials and Methodssupporting
confidence: 95%
“…Compound O,O-diethyl S-hydroxymethyl phosphorodithioate (VI) was detected as a conjugated metabolite, and its concentration was 0.004 ppm ( Table 7). This result agrees with some previous studies, 5,33,34 which noted that in adult rats, prothiofos gave prothiofos oxon, O-ethyl phosphoric acid, and 2,4-dichlorophenole. Fenitrothion insecticide was converted to phosphorothioate and dimethylphosphate.…”
Section: ■ Materials and Methodssupporting
confidence: 95%
“…Bound 14 C-fenitrothion and 14 C-pirimiphos-methyl in maize seeds proved to be highly bioavailable to rats. The data obtained are in line with many recent studies which indicate a moderate to high bioavailability of soybean bound residues of pirimiphos-methyl (38) , chlorpyrifos (39) , dichlorovos (40) , fenitrothion (41) and canola bound residues of prothiofos (33) .…”
Section: Bioavailability To Ratssupporting
confidence: 79%
“…Zayed et al, (2,30) showed that the amount of both 14 Ccarbofuran and 14 C-pirimiphos-methyl residues in soybeans oil decreased to 16 % and 25 %, respectively through the refining processes. It is also found that the complete refined sunflower oil obtained from treated sunflower plants lost about 64 % of the total 14 C-zineb residues in crude oil (34) and 69 % of 14 Cprothiofos residues in canola oil (33) .…”
Section: Effect Of Refining Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no Safework Australia exposure standard for 2‐chlorophenol, but it is known to be a respiratory and dermal irritant. Similar chemicals (eg, 2,4‐dichlorophenol) have been identified in canola oil as pesticide residue . Glycerine is a by‐product of biodiesel production, often manufactured from canola oil.…”
Section: Flavour Excipient Nicotine Hexa‐decanoic Acid Octa‐decanoic mentioning
confidence: 97%